Pemenuhan Hak Anak dalam Keluarga dengan Orang Tua Tunggal di Jambi: Tantangan dan Strategi - Wulandari, Tati (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2024)
This study aims to examine the fulfillment of children's rights in single-parent families in Jambi, including the rights to education, health, protection, economy, and social welfare. This research uses a qualitative approach with in-depth interviews, participatory observation, and documentation methods. The results of the study show that single parents face various challenges, such as financial limitations, inadequate access to health services, and social stigma. Nonetheless, they implement various strategies to fulfill children's rights, such as seeking help from the community and school scholarship programs. Observations in the home and school environment show support from the school in the form of tutoring and scholarships. The discussion of the results of this study underlined the need to increase the socialization of assistance programs, cooperation between the government, schools, and communities, and the provision of more accessible health services. The implications of this study show the importance of more comprehensive interventions and better coordination to ensure the fulfillment of children's rights in single-parent families in Jambi.